Preparing phenolic resins using pulping spent liquor. (September 2017) - Han, Qing; Li, Dongping; Li, Xinping; Peng, Xinwen; Zhang, Dapeng
Abstract: The method of using spent liquor (SL) obtained from the chemical pretreatment stage of wheat straw semi-chemical pulping to prepare spent liquor phenolic resins (SLPR) was investigated in the present work. In this work spent liquor was modified with phenol, and then the modified spent liquor was further synthesized with phenol and formaldehyde under appropriate conditions. Experimental data shows that the substitution mass fraction of spent liquor for phenol, the mole ratios of formaldehyde and sodium hydroxide to phenol, temperature and duration time of addition and condensation reaction all show significant influence on the properties of SLPR. SLPR and pure phenolic resins (PR) exhibited almost the same macromolecular structures characterized by FT-IR, and the main properties of the SLPR such as free formaldehyde content, gel time and bonding strength demonstrated superiority to that of PR.